EP1070 Risk-reducing salpingo-oophorectomy in Brca mutation carriers. a prospective multicentric study. (1st November 2019) - Del Vecchio, V; Loizzi, V; Cicinelli, E; Deromemaj, X; Kardhashi, A; Paradiso, A; Legge, F; Natalicchio, MI; Resta, L; Resta, N; Cormio, G
Abstract : Introduction/Background: Ovarian carcinoma is the leading cause of death among gynaecological malignancies, and there is a current lack of effective screening procedure. More than one-fifth of ovarian tumours have genetic predisposition and, in about 65–85% of these cases, the genetic abnormality is related to a germline mutation in Breast Related-Cancer Genes ( BRCA) 1 and 2 which are tumour suppressor-autosomal dominant inherited genes encoding proteins involved in homologous recombination. Different studies evaluated the origin of early High Grade Serous Ovarian Cancer (HGSOC) in the distant portion of the fallopian tube and this discovery led to develop a risk-reducing strategy through a prophylactic bilateral salpingo-oophorectomy (BSO) in women with BRCA1/2 genes mutation. Methodology: Risk-reducing surgery (RRS) was performed in 74 patients carrying BRCA1 (aged between 34–73 years, median age was 50 years) and BRCA 2 mutation (aged between 41–69 years, median age was 52 years). 39 patients had previous history of breast cancer. Results: Between the 74 patients, 58 women (78, 4%) underwent risk-reducing salpingo-oophorectomy (RRSO) through a laparoscopic minimally invasive approach, 5 (6, 7%) underwent laparoscopic RRSO and contextual hysterectomy, 1 woman (1, 4%) underwent RRSO through a laparotomic approach and 10 women (13, 5%) laparotomic RRSO and hysterectomy. During 2 (2, 7%) laparoscopic RRSO, prophylactic bilateral mastectomy was also performed. Early and late complication occurred in 3 patients (4%). 2 patients (2, 7%) were found to have occult Serous Tubal Intraepithelial Carcinoma (STIC) and 3 patients (4%) occult cancer. Conclusion: RRSO is safe and feasible in BRCA mutation carriers. The procedure is effective for genetic prevention of ovarian cancer. Disclosure: Nothing to disclose